Experimental and numerical design of renewable-energy-supported advanced biological wastewater treatment plant - Gurtekin, E. (Springer, 2019)
Nowadays biological wastewater treatment processes are more applied than other physical and chemical methods to the treatment of domestic wastewater. By the way, energy consumption plays an important role in wastewater treatment plants. In order to realize energy efficiency, the initial investment costs as well as the operating costs should be taken into account for new installations. Energy consumption can be saved, and the energy can be generated with the choice of mechanical equipment in the wastewater treatment plants, the optimum system design, the use of the organic content of the wastewater, supporting of renewable energy sources in the existing treatment area. In this study, an advanced biological wastewater treatment plant is selected in the city of Malatya. This plant is modeled by SASSPro numerical program. Then, the obtained numerical and experimental results are discussed and compared. These results show that numerical results are in good agreement with measurement one. Also, in order to meet the energy requirement of the proposed plant, renewable-energy-supported advanced biological wastewater treatment plant is modeled with Polysun software. A 2.85-MW photovoltaic panel, 107 thermal solar panels and 99-m-deep geothermal heat pump were used in this modeling. As a result of the modeling, annual electricity of 5,750,000kWh and 7,300,300 L hot water at 50 degrees C are obtained. Hot water can be used for heating the wastewater and can be used for drying purposes.
Keywords: Wastewater; SASSPro; Renewable energy; Treatment